KEMAMPUAN MENENTUKAN PANTUN DENGAN MENGGUNAKAN METODE NUMBERED HEADS TOGETHER (NHT) PADA SISWA KELAS X SMA NEGERI 12 BURU - Musyawir, Musyawir; Jufri Sabtu,; Wafatima, Wafatima (Journal of Innovation Research and Knowledge, 2023)
Students' ability in writing rhymes is still lacking. This is mainly due to students' lack of interest in learning. The world of literature for students is still a foreign world and only certain people enter, other problems faced by students include: 1) students find it difficult to issue ideas / ideas that will be put in writing, 2) lack of mastery of vocabulary, 3) difficult to compose sentences in Indonesian that are good and correct. To improve the ability to write poetry, it is necessary to find a solution in the form of a learning method. One of the learning methods that can be applied is the Numbered Heads Together method). In general, Numbered Heads Together is used to involve students in strengthening learning understanding or checking students' understanding of learning material. This study aims to describe the ability to determine rhymes using the Numbered Heads Together Method in Class XSMA Negeri 12 Buru Students. This study was designed using quantitative descriptive methods. Data were collected through research instruments in the form of tests and analyzed using statistical techniques. The results showed that of the 17 research samples who obtained scores of 65 and above were 3 students or 17.6% and the research samples who obtained scores less than 65 were 14 students or 82.3%. Based on the mastery criteria that the research sample is successful if 85% of students get a score of 65 and above, it can be concluded that class X students of SMA Negeri 12 Buru have not been able to determine pantundans using the Numbered Heads Together Method.